1984
DOI: 10.1136/jnnp.47.7.686
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic gastroparesis from autonomic neuropathy: surgical considerations and changes in vagus nerve morphology.

Abstract: SUMMARY Two cases with intractable vomiting due to gastroparesis, a rare feature of diabetic autonomic neuropathy, are described. Both required surgical treatment. In the first a gastroenterostomy was complicated by reflux gastritis requiring a revision operation; in the second a gastrojejunostomy was successful. Electron microscopic studies of the vagus nerve in one of the cases showed a severe reduction in the density of unmyelinated axons, the surviving axons tending to be of small calibre. The severity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 13 publications
3
48
0
1
Order By: Relevance
“…Plasma gastrin concentrations were also increased in dogs after vagotomy [29]. Studies have shown that there was a significant difference in gastrin plasma concentrations before and after vagotomy [30][31][32].…”
Section: Discussionmentioning
confidence: 95%
“…Plasma gastrin concentrations were also increased in dogs after vagotomy [29]. Studies have shown that there was a significant difference in gastrin plasma concentrations before and after vagotomy [30][31][32].…”
Section: Discussionmentioning
confidence: 95%
“…Feldman et al found a reduced gastric acid response to sham feeding in diabetic patients, suggesting vagal neuropathy [3]. Pathologic specimens, when obtained, have shown evidence of vagal degeneration [19]. In this study, we used the pancreatic polypeptide response in response to sham feeding as a measure of vagal efferent function [4,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a relatively poor correlation between gastric emptying and cardiovascular autonomic nerve dysfunction [7,8]. In animal models of diabetes, the neural innervation and neuropeptide content of the gastrointestinal tract is abnormal [41] and in preliminary human studies a decrease in the density of unmyelinated axons in the abdominal vagus was observed [42]. However, a more detailed study found no abnormalities in the gastric wall, or abdominal vagus in patients with diabetic gastroparesis [43].…”
Section: Pathogenesis -Impact Of Blood Glucose Concentrationmentioning
confidence: 99%